Single-cell transcriptomics in colorectal cancer uncover the potential of metastasis and immune dysregulation of a cell cluster overexpressed PRSS22 - Xu, Chengyuan; Zhou, Ziheng; Zhu, Dongfei; Zhang, Qingyun; Zhong, Shoubin; Li, Zhenhua (Frontiers in Immunology, 2025)
BackgroundColorectal cancer (CRC) is one of the most common malignancies worldwide, and its complex pathogenesis and significant tumor cell heterogeneity remain major challenges. With the rapid development of single-cell sequencing technology, we can now delve deeper into the cellular composition and dynamic changes within the tumor microenvironment, revealing cellular interactions and their potential roles in tumorigenesis.MethodIn this study, we systematically analyzed comprehensive single-cell RNA sequencing data from 25 colorectal cancer and 10 adjacent normal tissue samples. We explored the characteristics and biological significance of tumor cell subpopulations, performed quality control, dimensionality reduction, and cell type identification, and further investigated epithelial cell copy number variations, cell communication, and pseudotime analysis. Subsequently, Boruta feature selection algorithm was combined to identify prognosis related genes. The expression patterns, clinical significance and biological effects of PRSS22 were validated in vitro.ResultsOur analysis found an epithelial cell subcluster with high expression of PRSS22 exhibited high proliferation and migration abilities, and it was also associated with the dysregulated immune microenvironment. After further experimental verification, we proved the high expression patterns and clinical significance of PRSS22. Downregulation of PRSS22 in CRC cells resulted in a reduction of proliferation, migration and invasion.ConclusionOur study has identified a cell subcluster that is closely linked to progression, immune dysregulation and prognosis in CRC, and we have also identified PRSS22 as its hub gene that has great potential to become a new immunotherapeutic targets target for CRC.